2007
DOI: 10.1590/s0100-84042007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Variações sazonais nas concentrações de pigmentos e nutrientes em folhas de espécies de cerrado com diferentes estratégias fenológicas

Abstract: -(Seasonal variations in leaf pigments and nutrients in "cerrado" species with different phenological patterns). Several studies have been trying to establish relationships between environmental conditions and leaf traits. In the present study, concentrations of pigments (chlorophylls a, b, carotenoids and anthocyanins), N and P and specific leaf area (SLA) were measured in leaves of six "cerrado" species (three deciduous and three evergreen species) in two cerrado stricto sensu sites with differences in canop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
(35 reference statements)
2
13
0
9
Order By: Relevance
“…Climate seasonality is an important determinant of phenological events, having a direct impact on metabolic and regulating processes such as germination, sprouting, senescence, flowering, and fruiting (Taiz and Zeiger 2013). Plant response to seasonality effects has been widely studied in northern ecosystems (Chapin III 1980), Mediterranean (Valladares et al 2000), and other strongly seasonal ecosystems, such as the Brazilian cerrado (Carvalho et al 2007), where the vegetation is subjected to severe resource constraints during a period of the year and shows morphophysiological variations. The ecophysiology of plants from subtropical forests, where the transition between seasons is gradual, has not been studied in depth up until now, and general data on subtropical forests are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Climate seasonality is an important determinant of phenological events, having a direct impact on metabolic and regulating processes such as germination, sprouting, senescence, flowering, and fruiting (Taiz and Zeiger 2013). Plant response to seasonality effects has been widely studied in northern ecosystems (Chapin III 1980), Mediterranean (Valladares et al 2000), and other strongly seasonal ecosystems, such as the Brazilian cerrado (Carvalho et al 2007), where the vegetation is subjected to severe resource constraints during a period of the year and shows morphophysiological variations. The ecophysiology of plants from subtropical forests, where the transition between seasons is gradual, has not been studied in depth up until now, and general data on subtropical forests are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al (2007) have also shown that leaves collected during the rainy season had higher rates of N and P compared to those collected in the dry season. Another factor that might have indirect influence on F. mannifera is the sprout of leaves during the dry-rain transition because young leaves tend to have higher nutrient leaching as a result of the rains.…”
Section: Discussionmentioning
confidence: 91%
“…Foliar characters are often used as indicators of the relationship between the use of resources by plants, their biomass and the ecosystem functioning (Craine, Froehle, Tilman, Wedin, & Chapin, 2001). Studies have sought to establish relationships between environmental conditions and foliar properties, although leaf characteristics are usually measured at the peak of the growing season when environmental conditions favor carbon assimilation and there is an abundance of expanded and healthy leaves (Carvalho, Bustamante, Kozovits, & Asner, 2007), with scarce work conducted in savanna environments. In these ecosystems, low water availability, soil nutrient deficiencies and fire are the main causes of instability in final productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Pilon, Udulutsch, and Durigan (2015) studied the phenological patterns of 111 cerrado species, indicating that the mangabeira is a semideciduous or deciduous species that loses leaves during the dry season of the year, agreeing with Lorenzi (2000), and A. V. Pereira, E. B. C. Pereira, and Silva Júnior (2010). According to Carvalho et al (2007), who analyzed the concentration of pigments and nutrients in leaves of cerrado species with different phenological strategies, detected no differences in the behavior of deciduous and evergreen plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation